2007
DOI: 10.2478/s11536-007-0018-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing donor selection in order to establish a cord blood banking facility: maternal and obstetric factors impact

Abstract: AbstractIn this study, we analyzed the obstetric factors affecting total nucleated cells (TNC) content of cord blood units to establish the criteria for umbilical cord blood (UCB) donor selection in our geographic area.UCB was collected from normal uncomplicated pregnancies. In every case, following data were recorded: (1) gestation length; (2) type of delivery (cesarean or vaginal); and (3) newborn characteristics: weight and sex. For each sample, TNC content,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…A longer gestational period was associated with a higher TNC count . It has been shown that each additional week of gestation is associated with a 3% increase in TNC .…”
Section: Gestational Periodmentioning
confidence: 94%
See 4 more Smart Citations
“…A longer gestational period was associated with a higher TNC count . It has been shown that each additional week of gestation is associated with a 3% increase in TNC .…”
Section: Gestational Periodmentioning
confidence: 94%
“…Chivu et al. found that maternal age inversely influenced the TNC count . However, several studies have indicated that maternal age has no effect on laboratory parameters of CB …”
Section: Maternal Factorsmentioning
confidence: 99%
See 3 more Smart Citations